Phonological Contrast Between English Language and Baggara Arabs dialect - Musa Alamin Hamouda (Universitas Lambung Mangkurat, 2023)
Abstract:- This study investigates the similarities and differences between Baggara Arabs dialect and English language phonological systems. It aims at preparing a scale for the difficulties of English pronunciation that face Baggara Arabs students, as well as enabling Baggara Arabs learners of English Language to pronounce English sounds or phonemes and words accurately. It uses the semi-experimental approach . In addition pre and post-tests are used as tools for gathering data. 30 secondary school students were chosen as a reasonable sample to represent the secondary school students at Elddein locality in East Dar Fur State. The study comes out with many results: The phonological rules of English facilitates Baggara students to speak and pronounce English fluently. The phonological system of English is different from Baggras dialect and that they undergo some difficulties. The recommendations of the study are listed as: The researchers should get benefit from this study in contrastive analysis in other dialects to establish inter-lingual identifications between the L1 and the L2. They should also get benefit from the prediction of learning problems that they face while learning English language (Phonology an Phonetics). This study can also be used as a reference study to accomplish more and deep studies on other tribal dialects in Sudan.